2016
DOI: 10.1016/j.bbmt.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intensive Chemotherapy and Hypomethylating Agents before Allogeneic Stem Cell Transplantation for Advanced Myelodysplastic Syndromes: A Study of the Myelodysplastic Syndrome Subcommittee of the Chronic Malignancies Working Party of the European Society for Blood and Marrow Transplant Research

Abstract: The European Society for Blood and Marrow Transplant Research data set was used to retrospectively analyze the outcomes of hypomethylating therapy (HMA) compared with those of conventional chemotherapy (CC) before hematopoietic stem cell transplantation (HSCT) in 209 patients with advanced myelodysplastic syn-dromes. Median follow-up was 22.1 months and the median age of the group was 57.6 years with 37% of the population older than > 60 years. The majority of patients (59%) received reduced-intensity conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
6
30
0
3
Order By: Relevance
“…However, a recent study by Potter et al using a large registry data suggested that, unlike for patients with primary refractory disease, the post-transplant outcomes of patients with MDS not in CR were not significantly worse than those in CR [24]. This is in line with our results which showed that continued marrow response even without HI at HSCT was an independent predictor of a favorable prognosis, and that CR was not a prerequisite for prolonged survival.…”
Section: Discussionsupporting
confidence: 91%
“…However, a recent study by Potter et al using a large registry data suggested that, unlike for patients with primary refractory disease, the post-transplant outcomes of patients with MDS not in CR were not significantly worse than those in CR [24]. This is in line with our results which showed that continued marrow response even without HI at HSCT was an independent predictor of a favorable prognosis, and that CR was not a prerequisite for prolonged survival.…”
Section: Discussionsupporting
confidence: 91%
“…Частота ответов на ГМП сопоставима с данными, полученными в исследованиях других авторов [13][14][15][16][17].…”
Section: обсуждение и заключениеunclassified
“…Так, сообщается о преимуществах у пациентов с моносомией/делецией хромосомы 7 при лечении азацитидином [20]. В литературе глубокому анализу подвергается прогностическое значение цитогенетических аномалий [14,21]. В проведенном нами многофакторном анализе влияние цитогенети-ческих изменений не было статистически значимым.…”
Section: обсуждение и заключениеunclassified
See 1 more Smart Citation
“…Dec therapy was shown to be associated with reduced incidence of GvHD, lower relapse rate, and increased overall survival with acceptable tolerance. [6][7][8][9] Thus, Dec may be an ideal candidate for use in combination with standard preparative regimen for patients scheduled to undergo allo-HSCT. In this study, we retrospectively evaluated the efficacy and safety of Dec-containing conditioning regimen in 76 patients with intermediate-or high-risk MDS/AML.…”
Section: Introductionmentioning
confidence: 99%